2016
DOI: 10.1371/journal.pntd.0004406
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptomic Exploration Reveals Unique Molecular Adaptations of Neuropathogenic Trichobilharzia to Invade and Parasitize Its Avian Definitive Host

Abstract: To date, most molecular investigations of schistosomatids have focused principally on blood flukes (schistosomes) of humans. Despite the clinical importance of cercarial dermatitis in humans caused by Trichobilharzia regenti and the serious neuropathologic disease that this parasite causes in its permissive avian hosts and accidental mammalian hosts, almost nothing is known about the molecular aspects of how this fluke invades its hosts, migrates in host tissues and how it interacts with its hosts’ immune syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 101 publications
2
32
0
Order By: Relevance
“…These proteases are highly expressed in migrating schistosomula [50, 51] and can get in contact with the adjacent nervous tissue either when the parasite regurgitates (TrCB1.1 as a digestive enzyme, [18]) or when it struggles through the tissue (TrCB2 as a neurohistolytic enzyme, [13]). In our recent work [17] it remained questionable if secretions of schistosomula may be involved in the CNS pathogenesis, particularly in activation of glial cells.…”
Section: Discussionmentioning
confidence: 99%
“…These proteases are highly expressed in migrating schistosomula [50, 51] and can get in contact with the adjacent nervous tissue either when the parasite regurgitates (TrCB1.1 as a digestive enzyme, [18]) or when it struggles through the tissue (TrCB2 as a neurohistolytic enzyme, [13]). In our recent work [17] it remained questionable if secretions of schistosomula may be involved in the CNS pathogenesis, particularly in activation of glial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, pepsin-processed enzymes were used in most experiments. The asparaginyl endopeptidase (AE, legumain) was confirmed as an endogenous trans-processing enzyme activating other digestive peptidases in human schistosomes (Sajid et al, 2003) and three transcripts coding this enzyme were also found in T. regenti transcriptome (Leontovyč et al, 2016(Leontovyč et al, , 2019. We were able to trans-process the pro-TrCB1 using tick IrAE, obtaining several intermediates during short-time incubations, but this method was not widely used in our experiments, since it provided low yields.…”
Section: Discussionmentioning
confidence: 96%
“…Cathepsins B also act as potent (carboxy-) exopeptidases (Illy et al, 1997). Several transcripts of cathepsin L and D genes were found also in the transcriptome of T. regenti schistosomula (Leontovyč et al, 2016).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations